The Impact of Computer Use on Employee Performance in High-Trust Professions: Re-Examining Selection Criteria in the Internet Age. - MULLEN, JOHN K. (Journal of Applied Social Psychology, 2011)
Exposure to digital media is reconfiguring the neural networks of young people, possibly at the expense of empathy and social skills. Extraverts with high self-esteem and certain personality traits tend to initiate face-to-face (FtF) contact with strangers; introverts lower in self-esteem use computer-mediated communication (CMC). Those who are overreliant on CMC miss nonverbal cues indicating deception and insincerity. This research suggests that many who have been raised in the Internet Age may be ill suited for high-trust professions involving the establishment of FtF relationships. Greater use of psychological tests and observations of applicants engaged in behaviors that reveal desired personality traits are in order.